Mathematical Modeling of Solar Photovoltaic Module to generate Maximum Power Using Matlab/Simulink - Amusat Ramoni Olawale; Sulaimon Shodiya; Yakubu H Ngadda (Jurnal Internasional Penelitian Teknologi Terapan, 2021)
Modeling is a basic tool of the real system simulation in translating the Mathematical results into real life. In this study, the Modeling and simulation of photovoltaic Module type PS-P310-36 were developed, and maximum power was obtained. The output I – V and P – V curves of the model were studied and analyzed under different irradiance (200 W/m2, 400 W/m, 600 W/m2, 800 W/m, and 1000 W/m2) at a constant temperature of 25oC. The model attained maximum power of 308, 251.6, 191.4, 129.2, and 64.74 W at 1000, 800, 600, 400, and 200 W/m2 irradiance, respectively. The model results agreed with the characteristics curves of the PV module of previous similar PV studies. The proposed model will serve as quick tools for designers in obtaining the maximum power of PV at distinct irradiance. However, for a more accurate design, more information is needed.